Administration patterns of magnesium sulphate for women with preeclampsia and immediate newborn outcomes in Kawempe National Referral Hospital-Uganda: a cohort study - Mariam Birungi; Jane Nakibuuka; Mark Kaddumukasa; Josephine Najjuma; Christopher J. Burant; Shirley Moore; Carol Blixen; Elly T. Katabira; Martha Sajatovic; Scovia Nalugo Mbalinda (BMC, 2024)
Abstract Background Preeclampsia is the second leading cause of maternal death in Uganda. WHO recommends using magnesium sulphate (MgSO4) to prevent and treat preeclampsia with severe features (PEC) and eclampsia. MgSO4 is used to prevent eclampsia and treat women who experience an eclamptic convulsion to avoid severe maternal/infant illnesses and death. We set out to assess MgSO4 administration patterns in women with PEC or eclampsia and the immediate newborn outcomes of neonates. Methods This was an analytical observational cohort study at Kawempe National Referral Hospital in Uganda. Two hundred ten pregnant mothers with PEC or eclampsia were recruited in the study after receiving the loading dose of MgSO4 and then followed through labour and delivery to observe MgSO4 administration patterns and immediate newborn outcomes using Apgar and Thompson scores. SPSS version 23 was used to analyse data, and both bivariate and multivariate logistic regressions were used to determine factors associated with the low Apgar score at five minutes. Results Overall, majority of the patients received more than one dose with 33.3% received a sixth dose of MgSO4. The majority, 84.8%, of the mothers delivered live babies, 31.0% babies had complications, and were admitted to the neonatal intensive care unit (NICU). NICU admissions were mostly due to respiratory distress21.4%, preterm delivery21.0%, and 5.5% died within seven days. Majority 93.3% of the newborns had an Apgar score of seven and above at five minutes, of the newborns who were Thompson scored, 70.4% scored between 1 to 10 which is mild HIE. Initiation of MgSO4 treatment within one hour from prescription (AOR = 0.49, CI: 0.01-1.94), 4-hourly timing of the first maintenance dose (AOR = 0.22, CI: 0.06-0.79) and having complete doses of MgSO4 treatment (AOR = 0.89, CI: 0.03-3.05) decreased the likelihood of having low Apgar scores at five minutes. Conclusions Timely administration of the first maintenance dose of MgSO4 decreases the likelihood of low Apgar score at 5 min and NICU admission in newborns, and most NICU admissions were due to respiratory distress and preterm delivery.